2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16597
|View full text |Cite
|
Sign up to set email alerts
|

Problem Based Learning In An Undergraduate Electrical Engineering Course

Abstract: Her research interests include problem-based and case-based pedagogy in teacher education and science, interactive multimedia environments, scientific literacy, and cultural and gender influences in confidence. She is a co-PI on two National Science Foundation-funded projects involving multimedia case-based learning environments in science, and research on problem-based models of professional development in science. Address: N8423 1251 St., River Falls, WI 54022, phone:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Since PBL was posted in the 1960s in response dissatisfaction with traditional medical education, scholars have found that PBL can contribute to knowledge retention, student satisfaction, motivation, and critical thinking from many perspectives on teaching [24][25][26][27][28] In addition, PBL is currently widely used in North America and Asia, and PBL is considered a successful implementation of current medical education, but the utilization of PBL is different in different regions, showing no difference in geographical origin [29]. Even though some studies have been published, the heterogeneity within the method, region, individuals and outcomes left some difficulties for medical educational researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Since PBL was posted in the 1960s in response dissatisfaction with traditional medical education, scholars have found that PBL can contribute to knowledge retention, student satisfaction, motivation, and critical thinking from many perspectives on teaching [24][25][26][27][28] In addition, PBL is currently widely used in North America and Asia, and PBL is considered a successful implementation of current medical education, but the utilization of PBL is different in different regions, showing no difference in geographical origin [29]. Even though some studies have been published, the heterogeneity within the method, region, individuals and outcomes left some difficulties for medical educational researchers.…”
Section: Discussionmentioning
confidence: 99%
“…There are two equally probable explanations of this student confusion. First, students could prefer and/or expect traditional lecturing and resist active-learning strategies, like collaborative learning ( Lake, 2001 ; Yadav et al. , 2010 ; Tharayil et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have also provided examples of how to reduce resistance to learning activities, such as giving students feedback and support throughout the activity (Yadav, Lundeberg, Subedi, & Bunting, 2011), clearly explaining the purposes and expectations of the activity (Strobel & van Barneveld, 2009), making the activity more enjoyable (Stover & Holland, 2018), and aligning the activity with other course assessments (Bentley, Kennedy, & Semsar, 2011). Most of these studies have been qualitative, and have focused on resistance to an unknown activity.…”
Section: Model and Hypotheses: Drivers And Inhibitors Of Resistancementioning
confidence: 99%